Optical cleanliness measurement methods for aluminium sheet surfaces. (26th September 2018) - Wang, Junjie; Andrews, Peter; Butler, Colin; McAlpine, Eoghan; Scamans, Geoff; Zhou, Xiaorong
Abstract : The cleaning of rolled aluminium surfaces is of critical importance for most applications and is of particular importance in automotive applications. The cleanliness of the sheet surface is mainly determined by the residual amount of the near‐surface deformed layer on the alloy surface. This layer has nano‐sized grains with their grain boundaries decorated and pinned by oxide particles and lubricant residues. The deformed layer reduces the reflectivity of the sheet or strip surface to visible light, particularly in the short wavelength range, resulting in a brownish appearance. Based on the optical characteristics of the deformed layer, the use of optical microscopy, spectrophotometry, and colourimetry has been evaluated to provide a quantitative measurement of the level of cleanliness. These latter evaluations have been cross‐checked by using scanning electron microscopy and transmission electron microscopy on ultramicrotomed cross sections of aluminium sheet samples subjected to different level of cleaning to determine the amount of residual near‐surface deformed layer.